2014
DOI: 10.1113/jphysiol.2014.271098
|View full text |Cite
|
Sign up to set email alerts
|

The role of hydrogen sulphide in the control of breathing in hypoxic zebrafish (Danio rerio)

Abstract: Key pointsr Hydrogen sulphide (H 2 S), a gaseous neurotransmitter, is involved in oxygen sensing in glomus cells, which are oxygen-sensing cells found in the mammalian carotid body.r Neuroepithelial cells (NECs) are oxygen-sensing cells of fish and are thought to be phylogenetic precursors of mammalian glomus cells; however, the oxygen-sensing mechanisms of these cells remain largely unknown.r Both adult and larval zebrafish responded to exogenous H 2 S by increasing ventilation in a dose-dependent manner; H 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 46 publications
8
51
0
1
Order By: Relevance
“…This smaller size possibly reflected posttranslational cleavage of CBS as reported in mammalian systems (9). Consistent with previous observations, the reduced cbsb mRNA expression by morpholino knockdown [Kumai et al (13); Porteus et al (33)] also resulted in a reduction in its protein expression (Fig. 8E).…”
Section: The H 2 S-biosynthesis Enzyme Cbsb Is Expressed In Ionocytessupporting
confidence: 80%
See 3 more Smart Citations
“…This smaller size possibly reflected posttranslational cleavage of CBS as reported in mammalian systems (9). Consistent with previous observations, the reduced cbsb mRNA expression by morpholino knockdown [Kumai et al (13); Porteus et al (33)] also resulted in a reduction in its protein expression (Fig. 8E).…”
Section: The H 2 S-biosynthesis Enzyme Cbsb Is Expressed In Ionocytessupporting
confidence: 80%
“…As reported previously [Kumai et al (13); Porteus et al (33)], the CBSb morpholino was originally designed to splice out exon 3, but it appeared to reduce total CBSb mRNA levels, likely by premature mRNA degradation. In the present study, we further confirmed the effectiveness of the CBSb knockdown by Western blot using a specific antibody against the zebrafish CBSb.…”
Section: The H 2 S-biosynthesis Enzyme Cbsb Is Expressed In Ionocytesmentioning
confidence: 87%
See 2 more Smart Citations
“…Although there is an increasing awareness of the physiological significance of gasotransmitters in adult lower vertebrates (Fago et al, 2012;Olson et al, 2012), as in mammals, there are few data concerning their role during early development. To our knowledge, only two studies (Hedrick et al, 2005;Porteus et al, 2014) have systematically compared the interactive effects of gasotransmitters and developmental age and only one of these assessed the O 2 chemosensory response (Porteus et al, 2014). In that study, it was shown that endogenously produced H 2 S augmented the hyperventilatory response to hypoxia in both adult and larval (4 days post-fertilization, dpf) zebrafish, Danio rerio (Porteus et al, 2014).…”
Section: Introductionmentioning
confidence: 99%